2001
DOI: 10.1002/eqe.92
|View full text |Cite
|
Sign up to set email alerts
|

Comparing response of SDF systems to near‐fault and far‐fault earthquake motions in the context of spectral regions

Abstract: SUMMARYIn spite of important di erences in structural response to near-fault and far-fault ground motions, this paper aims at extending well-known concepts and results, based on elastic and inelastic response spectra for far-fault motions, to near-fault motions. Compared are certain aspects of the response of elastic and inelastic SDF systems to the two types of motions in the context of the acceleration-, velocity-, and displacement-sensitive regions of the response spectrum, leading to the following conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
169
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(182 citation statements)
references
References 9 publications
10
169
0
3
Order By: Relevance
“…Such pulse is typically observed at the beginning of the fault-normal (FN) ground velocity time-history and has a probability of occurrence that depends on the site-to-source geometry, earthquake magnitude and other parameters (Somerville et al 1997;Iervolino and Cornell 2008). Starting from the pioneer studies of Veletsos and Newmark (1960) and Bertero et al (1978), the response of yielding single-degree-of-freedom systems subjected to near-fault earthquake ground motions has been extensively studied (Chopra and Chintanapakdee 2003;Mavroeidis et al 2004 and references therein). Other studies focused on yielding frames and showed the potential of near-fault ground motions to induce large story drifts (Alavi and Krawinkler 2004;Makris and Psychogios 2006;Karavasilis et al 2010 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Such pulse is typically observed at the beginning of the fault-normal (FN) ground velocity time-history and has a probability of occurrence that depends on the site-to-source geometry, earthquake magnitude and other parameters (Somerville et al 1997;Iervolino and Cornell 2008). Starting from the pioneer studies of Veletsos and Newmark (1960) and Bertero et al (1978), the response of yielding single-degree-of-freedom systems subjected to near-fault earthquake ground motions has been extensively studied (Chopra and Chintanapakdee 2003;Mavroeidis et al 2004 and references therein). Other studies focused on yielding frames and showed the potential of near-fault ground motions to induce large story drifts (Alavi and Krawinkler 2004;Makris and Psychogios 2006;Karavasilis et al 2010 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Above ratios directly affect T e period (the period that distinct the acceleration-sensitive and velocity-sensitive zones in the response spectrum), and T d (the period that distinct the velocity-sensitive and displacement-sensitive zones in the response spectrum) and conclude that the velocity-sensitive zones become narrower and acceleration-sensitive and displacement-sensitive zones become wider [7]. In Figure 2.a.…”
Section: Directivity Effectmentioning
confidence: 93%
“…In order to capture the salient response features of pulses, several studies have examined the response spectra of single-pulse or separate pulse [16] [17], but a systematic analysis of the pulse parameters has not been performed.…”
Section: Elastic Spectrum Analysismentioning
confidence: 99%